Development and Characterization of Polymeric-based Biomaterial from Agro-food Waste: A Sustainable and Eco-friendly Approach Towards Plastic Pollution - Hussain, Rabbia; Aziz, Athar; Amin, Rashid; Khurshid, Asma (Current Pharmaceutical Biotechnology, 2025)
IntroductionCommercial plastics are potentially hazardous and can be carcinogenic due to the incorporation of chemical additives along with other additional components utilized as brominated flame retardants and phthalate plasticizers during production that excessively produce large numbers of gases, litter, and toxic components resulting in environmental pollution.MethodsBiodegradable plastic derived from natural renewable resources is the novel, alternative, and innovative approach considered to be potentially safe as a substitute for traditional synthetic plastic as they decompose easily without causing any harm to the ecosystem and natural habitat. The utilization of undervalued compounds, such as by-products of fruits and vegetables in the production of biodegradable packaging films, is currently a matter of interest because of their accessibility, affordability, ample supply, nontoxicity, physiochemical and nutritional properties. Industrial food waste was processed under controlled conditions with appropriate plasticizers to extract polymeric materials. Biodegradability, solubility, and air test analysis were performed to examine the physical properties of polymers prior to the characterization of the biofilm by Fourier-transformed infrared spectroscopy (FTIR) for the determination of polymeric characteristics.ResultsThe loss of mass examined in each bioplastic film was in the range of 0.01g to 0.20g. The dimension of each bioplastic was recorded in the range of 4.6 mm to 28.7 mm. The existence of -OH, C=C, C=O stretching, and other crucial functional groups that aid in the creation of a solid polymeric material are confirmed by FTIR analysis. This study provides an alternative approach for sustainable and commercially value-added production of polymeric-based biomaterials from agro-industrial waste as they are rich in starch, cellulose, and pectin for the development of bio-plastics.ConclusionThe rationale of this project is to achieve a straightforward, economical, and durable method for the production of bio-plastics through effective utilization of industrial and commercial fruit waste, ultimately aiding in revenue generation.
Keywords: agro-food waste